2016
DOI: 10.3109/01658107.2015.1118516
|View full text |Cite
|
Sign up to set email alerts
|

Macular Thickness in Subjective Memory Complaints and Mild Cognitive Impairment: A Non-Invasive Biomarker

Abstract: Alzheimer's disease (AD) is the main cause of dementia worldwide, which implies an important socioeconomic problem in developed countries. Efforts to find biomarkers to diagnose AD have been intensified, especially, to detect cognitive impairment in its early stages, also known as mild cognitive impairment (MCI). Besides, there are individuals referring memory loss that is unnoticeable in the family environment and presenting normal neuropsychological tests. The former patients are included in a clinical pictu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…In the present study, full‐thickness macular measurements were reduced in all ETDRS sectors of patients with MCI, although only the superior and inferior inner sectors were significantly thinner. Using spectral‐domain‐OCT, other authors have found reductions in full macular thickness in patients with MCI [30,46], but we believe the segmented inner retinal layers provide more reliable measurements. Both clinical and histopathologic studies have documented a preference for GCL impairment in AD [26,32,47,48].…”
Section: Discussionmentioning
confidence: 78%
“…In the present study, full‐thickness macular measurements were reduced in all ETDRS sectors of patients with MCI, although only the superior and inferior inner sectors were significantly thinner. Using spectral‐domain‐OCT, other authors have found reductions in full macular thickness in patients with MCI [30,46], but we believe the segmented inner retinal layers provide more reliable measurements. Both clinical and histopathologic studies have documented a preference for GCL impairment in AD [26,32,47,48].…”
Section: Discussionmentioning
confidence: 78%
“…Seven of the 15 studies evaluated macular volumes (subjects MCI:controls, 172:213) (25,30,32,34,37,38,40). In four of the seven studies, a statistically significant reduced macular volume was noted for MCI compared with controls (subjects MCI:controls, 106:91) (30,34,38), while three studies did not find differences (subjects MCI:controls, 66:122) (25,32,37). Thus, 61.6% of all MCI patients that had their macular volume measured had a statistically significant reduction in volume compared with controls.…”
Section: Macular Oct Resultsmentioning
confidence: 99%
“…Communication with the authors was attempted, but no clarification was possible ( 42 , 43 ). Finally, a total of 15 studies meeting inclusion criteria were evaluated and summarized ( 21 , 23 , 25 , 26 , 28 32 , 34 , 36 40 ) (see Figure 1 ). The general description and main findings of the included studies are described in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations